INFLUENCE OF BRAKE LIGHT LIGHT SOURCE ON DRIVER REACTION TIME (Perner's Contacts, 2020)
The paper deals with finding out the influence of the type of light source of car brake lights on the reaction time of the driver. The paper measures the reaction time of the driver in the form of depressing the brake pedal depending on the lighting of the brake lights on the driving vehicle. The evaluation of the measurement consists in a mutual comparison of the phase shift between the brake light signal of the first vehicle and the brake light signal of the second vehicle. The experimental measurement was performed for five people using a classic light bulb and then an LED diode at the brake lights of the first vehicle. From the measured waveforms, it was confirmed that the driver's reaction time depends on many factors, where the source and intensity of the brake lights also play an important role. At the same time, it affects the reaction time and the operation or inactivity of the rear position lamps. With their activation, the reaction time of the driver of the succeeding vehicle is extended.
Keywords: reaction time; car; brake light; safety